The Effect of Human Capital on Job Performance Mediated by Innovation Capability and Potential Absorptive Capacity - Pulatama, Ikmal Yasra; Ariadi, Gede (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of human capital on job performance, focusing on the mediating roles of innovation capability and absorptive capacity. Survey data from 80 PT Duniatex employees were analyzed using multiple regression and mediation analysis. Results show that human capital positively influences job performance, both directly and indirectly via the two mediators. These findings suggest that enhancing creativity, continuous learning, and knowledge absorption is essential for improving performance. Thus, human resource development should go beyond technical training to build innovation and adaptability in today’s dynamic business environment.